Proteomic studies of diauxic lag in the differentiating prokaryote Streptomyces coelicolor reveal a regulatory network of stress-induced proteins and central metabolic enzymes - Novotna, Jana; Vohradsky, Jiri; Berndt, Peter; Gramajo, Hugo; Langen, Hanno; Li, Xin-Ming; Minas, Wolfgang; Orsaria, Lelia; Roeder, Daniel; Thompson, Charles J (Molecular microbiology, 2003)
Bacteria typically undergo intermittent periods of starvation and adaptation, emulated as diauxic growth in the laboratory. In association with growth arrest elicited by metabolic stress, the differentiating eubacterium Streptomyces coelicolor not only adapts its primary metabolism, but can also activate developmental programmes leading to morphogenesis and antibiotic biosynthesis. Here, we report combined proteomic and metabolomic data of S. coelicolor used to analyse global changes in gene expression during diauxic growth in a defined liquid medium. Cultures initially grew on glutamate, providing the nitrogen source and feeding carbon (as 2-oxoglutarate) into the TCA cycle, followed by a diauxic delay allowing reorientation of metabolism and a second round of growth supported by NH4+, formed during prediauxic phase, and maltose, a glycolytic substrate. Cultures finally entered stationary phase as a result of nitrogen starvation. These four physiological states had previously been defined statistically by their distinct patterns of protein synthesis and heat shock responses. Together, these data demonstrated that the rates of synthesis of heat shock proteins are determined not only by temperature increase but also by the patterns and rates of metabolic flux in certain pathways. Synthesis profiles for metabolic- and stress-induced proteins can now be interpreted by the identification of 204 spots (SWICZ database presented at http://proteom.biomed.cas.cz). Cluster analysis showed that the activity of central metabolic enzymes involved in glycolysis, the TCA cycle, starvation or proteolysis each displayed identifiable patterns of synthesis that logically underlie the metabolic state of the culture. Diauxic lag was accompanied by a structured regulatory programme involving the sequential activation of heat-, salt-, cold- and bacteriostatic antibiotic (pristinamycin I, PI)-induced stimulons. Although stress stimulons presumably provide protection during environmental- or starvation-induced stress, their identities did not reveal any coherent adaptive or developmental functions. These studies revealed interactive regulation of metabolic and stress response systems including some proteins known to support developmental programmes in S. coelicolor.
Keywords: fyziologická adaptace; Proteome; uhlík; Carbon; Proteomics; Heat-Shock Response; kultivační média; proteomika; Culture Media; shluková analýza; Cluster Analysis; bakteriální proteiny; stanovení celkové genové exprese; Nitrogen; Gene Expression Regulation, Bacterial; regulace genové exprese u bakterií; proteiny teplotního šoku; Bacterial Proteins; Databases, Genetic; dusík; Heat-Shock Proteins; reakce na tepelný šok; proteom; Gene Expression Profiling; databáze genetické; Streptomyces; Adaptation, Physiological